The Role of Memorizing the Qur’an in Developing the Character of Students - Nurchayani, Fitri; Rusdin, Rusdin; Idhan, Mohamad; Azma, Azma (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2023)
This article examines the role of Qur’an Memorization in shaping students' characters at Banua Qur’an Palu. This article aims to explore the factors that influence the ability to memorize the Qur’an and the extent to which Qur’anic memorization can shape students' personalities. The research adopts a qualitative method with a case study approach. Data is collected through direct observation, in-depth interviews, and written document analysis. Data analysis techniques include data reduction, presentation, verification, and conclusion. The research findings indicate that the factors influencing the ability to memorize the Qur’an include internal and external factors. Qur’anic memorization can shape the students' personalities because the Qur’an contains verses that prohibit wrongdoing and encourage righteous deeds. These findings align with Tomas Lickona's theory, which suggests that good character can be developed through the habituation of good deeds in students' daily lives. This habituation is known as Moral Knowing, Moral Loving (Moral Feeling), and Moral Doing (Learning to Do). The implications of this research highlight the importance of continuous learning and guidance from religious teachers in shaping the students' characters.